Pre-Gondwanan-breakup origin of Beauprea (Proteaceae) explains its historical presence in New Caledonia and New Zealand - He, Tianhua; Lamont, Byron; Fogliani, B. (2016)
New Caledonia and New Zealand belong to the now largely submerged continent Zealandia. Their high levels of endemism and species richness are usually considered the result of transoceanic dispersal events followed by diversification after they re-emerged from the Pacific Ocean in the mid-Cenozoic. We explore the origin and evolutionary history of Beauprea (Proteaceae), which is now endemic to New Caledonia but was once spread throughout eastern Gondwana, including New Zealand. We review the extensive Beauprea-type pollen data in the fossil records and analyze the relationship of these fossil taxa to extant genera within Proteaceae. We further reconstruct the phylogenetic relations among nine extant species of Beauprea and estimate the age of the Beauprea clade. By incorporating extinct taxa into the Beauprea phylogenetic tree, we reconstruct the ancient distribution of this genus. Our analysis shows that Beauprea originated c. 88 Ma (million years ago) in Antarctica-Southeastern Australia and spread throughout Gondwana before its complete breakup. We propose that Beauprea, already existing as two lineages, was carried with Zealandia when it separated from the rest of Gondwana c. 82 Ma, thus supporting an autochthonous origin for Beauprea species now in New Caledonia and historically in New Zealand up to 1 Ma. We show that the presence of Beauprea through transoceanic dispersal is implausible. This means that neither New Caledonia nor New Zealand has been entirely submerged since the Upper Cretaceous; thus, possible vicariance and allopatry must be taken into account when considering the high levels of endemism and species richness of these island groups.